Financiamento dos programas federais de esporte e lazer no Brasil: 1995 - 2016 - Rosângela Gomes Pinali (2019)
This study investigates the amount of resources applied, through the budget of the Union, in sports and leisure policies from 1995 to 2016, trying to understand the way the theme was treated by the public power and what factors justified the priority of investments in this period. In this sense, the study is characterized as a quantitativequalitative research. Based on a documentary research on the budget execution of the programs and projects developed by the governments, it relates the amount invested with the political and administrative context of the managements carried out during the period and questions whether the federal public investment in sports and leisure contributed to the accomplishment of a policy of guarantee of rights. Through data collection in the Portal of the Chamber of Deputies and SIGA Brasil, it was possible to perceive that the budgetary distribution of the period revealed great oscillations, sometimes with privilege to the sport of participation and educational, or prioritizing the EAR. As a starting point, we highlight the administrative reform undertaken during the FHC period, which reduced the State's participation in the provision of social policies. From then on and during the Lula and Dilma governments, the main limitation observed originated in the practice of contingency of resources and in the low budget execution of the programs. In the first mandate of FHC it was not possible to define, through the collected data, the government's priority. In the second, it was verified that most of the authorized resources were spent in the Solidarity Sport program. As for the Lula government, the actions were directed, in the beginning, primarily, to the sports of participation and educational, through the programs PELC and PST. Since 2007 and during the Dilma government, the Pan American Games was focused on the preparation and accomplishment of major sporting events, with the objective of projecting the image of Brazil on the international scene, a perspective also aspirated by the government FHC. In this sense, even though the CF88 represents an important legal framework, what happens in certain periods is a greater allocation of resources in the EAR, privileging the interests of groups holding the economic power to the detriment of the actions of sport and leisure geared to the needs social rights. This change in trajectory contradicts and disrespects the provisions of the Charter that determines in paragraph II of Article 217 the allocation of public resources primarily for educational sport and only in specific cases for high-performance sport.